A contribuição da realidade virtual para o ensino e a aprendizagem de geometria espacial - Ferreira, Caroline Gomes (2023)
External evaluations demonstrate that high school students complete this stage of Basic Education with low proficiency in the knowledge object Spatial Geometry. The difficulty of visualizing geometric solids and the lack of depth in the subject are the causes most pointed out by the researchers as justification for this deficiency in student learning. The objective of this research is to analyze how the learning in Spatial Geometry of high school students occurs through the application of a proposal based on the construction of 3D videos focused on the use of Virtual Reality. Therefore, we opted for the study of the Prisms. The research is characterized as a Case Study. The study was structured in three (3) stages: planning, data collection and data analysis. The subjects are characterized by four students from different classes of the 1st grade of high school at a Public State School in the municipality of Cariré, one female and three males, all aged between 15 and 16 years. Data collection occurred in two stages. The first stage consisted of organizing the instruments and materials needed to carry out the study. In the second stage, data were collected for the research in three (3) phases. In the 1st phase, the previous knowledge that the students had about Prisms was verified through the application of a Survey Questionnaire. In the 1st phase, the previous knowledge that the students presented about Prisms were verified through the application of a Survey Questionnaire. The 2nd phase consisted of the application of a Didactic Sequence that contemplated 8 classes with 2h duration each and was subdivided into 3 distinct phases: Conceptual phase, Blender study phase and Virtual Reality use phase. In the 3rd phase, the knowledge that the students presented about Prisms was verified, after the application of this teaching methodology. Data analysis occurred through methodological triangulation, with the aid of the procedures proposed by Discursive Textual Analysis, in five (5) stages: unitarization, categorization, description, interpretation and argumentation. It was found that there was a qualitative leap in the learning of the individuals, when the knowledge of each subject was analyzed during the three evaluation processes (Application of the Survey Questionnaire, Didactic Sequence and Evaluation Questionnaire). It is noteworthy that when they were evaluated for the last time, the individuals who stated in the Survey Questionnaire did not know the concepts inherent to the Prisms, demonstrated the ability to develop coherent ideas later and students who had already established concepts began to bring them more impregnated with meaning, like what is conceptualized by the authors. The results obtained may contribute to the accomplishment of other researches related to the teaching of Spatial Geometry, as well as in studies related to the application of Virtual Reality in education, in addition to the implementation of Constructionism as a methodology of teaching and learning, expressed in the Didactic Sequence as an educational product. It is intended to present the results of this research in regional formations, as well as to publish the results in specific journals of the area. It is also aspired to expand this research through the preparation of a doctoral project.